Using an occupational perspective to understand behaviours fostering the prevention of work-related health problems: A proposed conceptual model. Issue 2 (2nd April 2020) - Lecours, Alexandra
ABSTRACT: Work is an occupation valued by billions of individuals across cultures and societies. As a determinant of health, work may have several positive effects on individuals' well-being. However, it may also have negative effects as accidents, physical illnesses, or transient mental disorders may occur. Workers' preventive behaviours appear to be a relevant means to help prevent work-related health problems, but no clear definition exists. An occupational perspective (Njelesani, Tang, Jonsson, & Polatajko, 2014) seems a promising way to understand the characteristics defining preventive behaviours at work. This study aimed to define preventive behaviours at work, in order to understand their operational characteristics. To achieve this aim, secondary qualitative analysis based on data collected during three prior studies was conducted. Six types of preventive behaviours were identified. Those are realized into a context, which involves several factors related to the person, occupation and environment. Results also suggest those behaviours may lead to positive outcomes on different health indicators. Interpretation of results according to the five dimensions of the occupational perspective led to a proposed Model of Preventive Behaviours at Work. This study demonstrates how occupational science might increase understanding of the engagement of individuals in their actions, in relation to their context. It also shed light on how doing can contribute to health and well-being, in an application related to the occupation of work.